Synthesis of Vulcanized Silica and Its application in Removing Hg(II) and Pb(II) From Water Samples - Madrakian, T.; Zolfigol, M.A.; Afkhami, A.; Eizadi, M.; Afshar, S. (Asian Journal of Chemistry, 2016)
The ability of the newly synthesized vulcanized silica for removing Hg2+ and Pb2+ at different optimized conditions of concentrations, amounts of absorbent and pH has been studied. Maximum adsorption for both the cations has been obtained at nearly neutral pH. Flame atomic absorption spectrometry was used for measuring lead and mercury concentration in stripped solutions. The isotherm curves for adsorption of two cations were obtained.